PEROBVC Estimating Method - Perovic, G. (Research Developments in Science and Technology Vol. 5, 2022)
A sequence of empirical variances have often appeared as a mixture of two or more sequences of empirical variances. These sequences have different distributions. Then a problem how to estimate the variance of basic distribution arises. A mixed distribution of empirical variances, composed of two distributions the basic and contaminating ones, and referred to as Perg mixed distribution of empirical variances, is considered. In the paper a robust inverse problem solution is given, namely a (new) robust method for estimation of variances of both distributions – Perobvc Method, as well as the estimates for the numbers of observations for both distributions and, in this way also the estimate of contamination degree.